THE READINESS OF HUMAN CAPITAL AND BIG DATA ANALYTICS IMPLEMENTATION FACING THE INDUSTRY REVOLUTION 4.0 (CASE: HUMAN CAPITAL IN HCBP CENTER OF PT. TELEKOMUNIKASI INDONESIA BANDUNG) (The Indonesian Journal of Business Administration, 2020)
The purpose of this research is to identify and analyzing the readiness of human capital and big data analytics implementation in the HCBP Center unit of PT. Telekomunikasi Indonesia Bandung in facing the industry revolution 4.0. To assess readiness in the face of industry 4.0, human capital has four factors that related to industry 4.0: knowledge, hard skills, soft skills, and attitude. Furthermore, big data analytics implementation in human capital has five factors that related to industry 4.0: data quality, analytical competencies, skilled workforce analytics leaders, the right mix of skills, and right analytics technology and data.This research used a quantitative data approach. Quantitative data is done by distributing questionnaires to employees who are respondents. Questionnaire data that has been collected that has passed the validity and reliability test. Then the data will be measured using the Geometric Mean formula to measure the gap analysis of each statement in each factor. Then, to measure the readiness of the overall construct using the Human Development Index (HDI).The results of this study indicate that the readiness of big data analytics implementation in human capital in the HCBP Center unit of PT. Telekomunikasi Indonesia Bandung is fully ready in all of factors such as data quality (optimal level), analytical competencies (receptive level), skilled workforce analytics leaders (optimal level), the right mix of skills (receptive level), and right analytics technology and data (optimal level). And the readiness of human capital in the HBCP Center unit of PT. Telekomunikasi Indonesia Bandung is not fully ready to face industry 4.0. There are two factors that have a value below the Ready level, namely hard skills (not ready level) and attitude (preliminary level). Therefore, researchers provide recommendations for companies. They must prepare the human capital by building attitudes and behavior that are oriented towards the use of digital technology in carrying out various daily activities and not just the implementation of the latest digital technology and company can also create learning and development programs that are digital or online.Keywords: Readiness, Human Capital, Big Data Analytics, Industry Revolution 4.0.